Pemanfaatan Sari Nenas Sebagai Sumber Energi Alternatif Pembuatan Bio-Baterai - Masthura Masthura; Abdullah Abdullah (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
Research has been carried out on the manufacture of biobatteries using pineapple extract. This research aims to determine the effect of volume variations of pineapple extract solution on the voltage and current produced by biobattery. Volume variations of pineapple extract solution consisted of 50 ml, 100 ml, 150 ml, 200 ml and 250 ml. The electrodes used were copper (Cu) and zinc (Zn), the tests carried out consisted of measurements of pH, voltage, current, electric power and the length of time the voltage was lowered. The test results for the pH value of the pineapple extract solution were 3.7. The highest value of voltage, current and electrical power is obtained in pineapple extract solution because the pineapple extract solution has a higher acidity value.